AB0421 Evaluation of The Experience, Satisfaction and Outcomes of An Autoinjector for Self-Administration of Subcutaneous Belimumab in Patients with Systemic Lupus Erythematosus (SLE). (15th July 2016) - Dashiell-Aje, E.; Harding, G.; Pascoe, K.; DeVries, J.; Berry, P.; Ramachandran, S.
Abstract : Background: A US, phase IIb study (#200339) found the belimumab autoinjector (BAI) was reliable and well-tolerated for home administration. This separate follow-up study (#201816) was conducted at the end of the phase IIb study to capture patient experiences with the various delivery devices-the BAI, intravenous belimumab (BIV) and belimumab prefilled syringe (BPS). Objectives: To assess patient experiences with the BAI, with belimumab in general, and with switching to the BAI from BIV or BPS. Preference for administration route and the impact on activities of daily living were also explored. Methods: Patients were recruited at their final week 8 study visit. The study consisted of a 43 item online (or paper) questionnaire followed by qualitative telephone interviews in a subset of patients. IRB approval was obtained and patients gave informed consent. The telephone interview captured further information from the patients' online survey responses. Quantitative data were analyzed using descriptive statistics and the qualitative data were transcribed and analysed using a content analysis approach. Results: This study included a total of 43 patients who were representative of those that completed the phase IIb BAI study. Patients reported a high level of confidence in their ability to use the BAI correctly the first time they used it on their own. Overall satisfaction and satisfaction with the frequency of administration was higher for the BAI compared with BIV, and 76% preferred the BAI. The BAI was considered more convenient than BIV due to shorter administration time, less travel time, less interference with work, portability, and less/no pain. In telephone interviews, 62% (n=13) reported some disadvantages with the BAI (discomfort, inconvenience, not ergonomic). Patients reported a high level of satisfaction with belimumab regardless of administration route; 74% were satisfied or very satisfied. All patients stated they would have preferred to initiate belimumab at an earlier stage of their disease and all patients wanted to continue receiving belimumab. The majority of patients reported improvements in overall symptoms, flare frequency and severity, and fatigue, since starting belimumab; many reported improvements in activities of daily living. Of those patients who worked, 59% reported the BAI had a positive impact on their ability to work and 40% of all patients reported the BAI improved their ability to carry out daily activities. Conclusions: Patients were positive regarding their experience with adding belimumab to standard of care therapies, and favoured the BAI over BIV administration. Given only 2 patients were on the BPS, it was hard to draw any meaningful conclusions for this group. Self-selection bias, recall bias and small sample size should be considered limitations of this study design. The results of this study suggest that the availability of the BAI will be a welcome treatment option. The potential benefits of the BAI identified in this study should be explored in a long-term evaluation of the device to assess clinical and patient reported outcomes. Role of the study sponsor statement: The research presented in this abstract was conducted by Evidera Inc. and was funded by GlaxoSmithKline. Disclosure of Interest: E. Dashiell-Aje: None declared, G. Harding: None declared, K. Pascoe: None declared, J. DeVries: None declared, P. Berry Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline during the conduct of the study, S. Ramachandran Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline during the conduct of the study